Maternal Death due to Delayed Management of Sigmoid Volvulus at 32 Weeks Pregnancy - k Adam, Gamal; Alhaj‌‌, Khalid; E.Elgaili, Samaual; M.Ahmed, Khalid Yassin; Miskeen, Elhadi (Gezira Journal of Health Sciences, 2015)
Colonic obstruction due to sigmoid colon volvulus during pregnancy is a rare but a serious complication with significant maternal and foetal mortality. We describe a case of sigmoid volvulus in a patient with 32 weeks of gestation that developed complete necrosis of the sigmoid colon who was admitted with 6 days of abdominal distension, vomiting, and the stoppage of the passage of gases and faeces with poor clinical conditions and signs of diffuse peritonitis. Abdominal ultrasound showed single viable foetus 32 weeks. Abdominal radiography showed severe dilation of the colon with horseshoe signal suggesting a sigmoid volvulus. The patient delivered vaginally 1.8 Kg male baby admitted to the nursery and passed later on from respiratory distress syndrome. With a diagnosis of complicated sigmoid volvulus, she underwent laparotomy where we found, an enormously distended sigmoid loop with gangrenous changes the sigmoid colon was resected and Hartman's procedure was performed. Poor postoperative recovery and the patient passed day 3 postoperativelyfrom septic shock